Regulatory Role of a Receptor-Like Kinase in Specifying Anther Cell Identity . Issue 3 (20th May 2016) - Yang, Li; Qian, Xiaoling; Chen, Mingjiao; Fei, Qili; Meyers, Blake C.; Liang, Wanqi; Zhang, Dabing
Abstract : The secretory peptide OsTDL1A interacts with LRR-RLK receptor MSP1 in regulating the formation of inner somatic layers and microsporocytes proliferation via modulating gene expression in rice. Abstract: In flowering plants, sequential formation of anther cell types is a highly ordered process that is essential for successful meiosis and sexual reproduction. Differentiation of meristematic cells and cell-cell communication are proposed to coordinate anther development. Among the proposed mechanisms of cell fate specification are cell surface-localized Leu-rich repeat receptor-like kinases (LRR-RLKs) and their putative ligands. Here, we present the genetic and biochemical evidence that a rice ( Oryza sativa ) LRR-RLK, MSP1 (MULTIPLE SPOROCYTE1), interacts with its ligand OsTDL1A (TPD1-like 1A), specifying the cell identity of anther wall layers and microsporocytes. An in vitro assay indicates that the 21-amino acid peptide of OsTDL1A has a physical interaction with the LRR domain of MSP1. The ostdl1a msp1 double mutant showed the defect in lacking middle layers and tapetal cells and having an increased number of microsporocytes similar to the ostdl1a or msp1 single mutant, indicating the same pathway of OsTDL1A-MSP1 in regulating anther development. Genome-wide expression profiles showed the altered expression of genes encoding transcription factors, particularly basic helix-loop-helix and basic leucine zipper domain transcription factors in ostdl1a and msp1 . Among these reduced expressed genes, one putatively encodes a TGA (TGACGTCA cis-element-binding protein) factor OsTGA10, and another one encodes a plant-specific CC-type glutaredoxin OsGrx_I1. OsTGA10 was shown to interact with OsGrx_I1, suggesting that OsTDL1A-MSP1 signaling specifies anther cell fate directly or indirectly affecting redox status. Collectively, these data point to a central role of the OsTDL1A-MSP1 signaling pathway in specifying somatic cell identity and suppressing overproliferation of archesporial cells in rice.